Infrastructure investment in Indonesia : a focus on ports (2019)
For Indonesia to join the top ten major global economies club by 2025, the average GDP per capita per annum would need to rise from USD 3,000 today to USD 15,000 and GDP per se to a heady USD 4.5 trillion (nearly five times the current GDP). It would need to do so in the space of less than ten years. To achieve this a two-pronged approach will be required: acceleration, and expansion. Underpinning such development is the need for strengthened connectivity not only throughout the archipelago, but also the Association of Southeast Asian Nations (ASEAN). Additionally, such development requires the strengthening of human resources capability, as well as the smart use of science and technology. Growth Centres, connectivity and infrastructure are considered the main building blocks of Indonesia’s economic corridors. This connectivity needs to be developed through ICT and ebusiness, improved logistics through transport and refined business policies—practices and processes such that international trade and investment grows commensurate with expectations. Currently logistics costs in Indonesia are a crippling 25% of GDP. Critical infrastructure needs and areas for improvement include: roads, seaports (ferries and container and bulk trade), airports, public transport via a modern metro system and connected rail freight routes.